Antibiotic Maximalism: Legislative Assaults on the Evidence-Based Treatment of Lyme Disease - Joseph B. Franklin (Washington University Law Review, 2012)
Antibiotics, and the deadly pathogens that have evolved to resist them, are one of the major public health concerns of our time. The introduction of penicillin in the early 1940s signaled a new era—not only for the treatment of devastating infections, but also for the out-witting of antibiotics by fast-evolving bacteria. If the middle of the twentieth century saw the era of antibiotic innovation, the past several years might be labeled the era of antibiotic resistance, when untreatable infections have become a modern scourge. Methicillin-resistant Staphylococcus aureus (MRSA) is the most notorious antibiotic resistant “superbug”; this antibiotic-resistent pathogen has emerged as an endemic problem in hospital and long-term care settings. In 2011, bills were introduced in both houses of Congress to encourage the development of new antibiotics to replace those that have become ineffective. Yet, unless or until a truly “miracle” antibiotic (i.e., one which may not be resisted by bacteria) is someday developed, the only solution to antibiotic resistance is to reduce the use of antibiotics. Surprisingly, amidst public-health efforts to prevent antibiotic-resistant pathogens by reining in excessive antibiotic use, several states have passed laws that legitimize intensive antibiotic regimens even when those regimens contradict the best available medical evidence. Although this unprecedented legislative activity has occurred in the context of a controversial medical diagnosis, chronic Lyme disease, the legal and political repercussions threaten the established role of state medical licensing boards in promoting evidence-based standardization of medical practice. The most intrusive of these statutes prevents state licensing boards from disciplining physicians who prescribe regimens of long-term antibiotic therapy that are specifically proscribed by mainstream clinical practice guidelines (CPGs) on Lyme disease treatment. Such laws promote the view of non-standard practitioners who favor the intensive, maximalist use of antibiotics for a condition that mainstream physicians dispute even exists. In an attempt to protect unnecessary antibiotic regimens, recent legislation legitimizes a treatment paradigm that poses an undue risk of harm to individual patients and to the public health. By enacting laws that protect and legitimize repudiated treatments, state legislatures have responded to a movement of non-standard “Lyme literate medical doctors” (LLMDs)—a movement that has been described as an “antiscience” and “parallel universe of pseudoscientific practitioners” by mainstream practitioners. In addition, by interfering with the legal authority of state medical boards to enforce evidence-based standards on antibiotic use, states have also sided with a fringe movement of physicians who oppose the “encroachment” of third-parties, including the government, upon the physician-patient relationship. These advocates decry the influence of evidence-based clinical guidelines and state medical licensing boards on the medical practice. Removing the power of state regulators to discipline physicians for dangerous, non-standard Lyme disease treatment is perceived as an opening salvo in the attack on the legitimacy of state medical oversight.
Keywords: antibiotics; lyme disease; discipline preemption; protection laws; politicization; maximalist